ELE Students’ Perceptions and Experiences on the Role of Intercultural Communication Course for Teaching Practice - Dara Suci, Aysah Asmo (Universitas Negeri Surabaya, 2023)
Intercultural communication plays a crucial role in today's diverse educational settings, where teachers are tasked with fostering inclusive and effective learning environments. This study explores the perceptions and experiences of English Language Education (ELE) students regarding the role of an Intercultural Communication Course (ICC) in their teaching practice. A qualitative research approach employing questionnaires was conducted with a sample of 27 ELE students of the 2019 cohort and also conducted semi-structured interviews with a sample of six ELE students of the 2019 cohort of one state university in Surabaya who had completed ICC in their fifth semester and also done their teaching practice of their teacher education program. The findings indicate that the ICC significantly impacted students' perceptions and experiences of their teaching practice. They reported enhanced awareness of their own cultural biases and increased self-reflection, leading to more inclusive instructional practices. Participants expressed improvements in their ability to facilitate communication and resolve conflicts arising from cultural differences. Moreover, the course was seen as instrumental in developing students' confidence, incorporating culturally relevant materials and activities into their lessons. However, some challenges were identified, including limited opportunities for practical application during the course and the need for continued support and training beyond the initial ICC. Participants emphasized the importance of ongoing professional development in intercultural communication skills and suggested integrating more experiential learning opportunities within the teacher education curriculum. Further research is needed to know how the lecturer perceives the Intercultural Communication Course (ICC). The future researcher is also expected to discover how to develop the right material for ICC for ELE students to support their teaching career as EFL pre-service teachers.